2D metal chalcogenides with surfaces fully covered with an organic "promoter" for high-performance biomimetic catalysis. Issue 70 (14th August 2019) - Li, Yanzhou; Shu, Jian; Huang, Qingqing; Chiranjeevulu, Kashi; Kumar, P. Naresh; Wang, Guan-E.; Deng, Wei-Hua; Tang, Dianping; Xu, Gang
Abstract : 2D catalytic materials whose inorganic surfaces are fully covered with pre-designed "promoter" groups showed excellent biomimetic catalytic activity. Abstract : A new series of 2D catalytic materials whose inorganic surfaces are fully covered with pre-designed "promoter" groups are reported. One of them showed excellent biomimetic catalytic activity and provided the lowest detection limit to glucose among the reported 2D materials and their composite materials.